MANAJEMEN PENDIDIKAN PESANTREN MODERN DALAM PEMBENTUKAN KARAKTER ANAK: Studi Kasus Pada Pondok Pesantren Modern Diniyyah Pasia Kabupaten Agam - Deded Sulaiman (IAIN Batusangkar, 2016)
Management Education Modern Islamic School in Kids Character Building: Case Studies in Modern Islamic Boarding Diniyyah Pasia Agam Regency. The issues raised in this paper is: How Management Education In Modern Islamic School Character Building Children?This research is a field of research by using qualitative approach. In these investigations the data to be collected is Pesantren Education Management Modern about Diniyyah Pasia Agam Regency of West Sumatra.From research conducted concluded that management leadership in Pondok Pesantren Modern Diniyyah Pasia is demokrastis leadership that characterized by the presence of consensus agreement in determining planing, organizing and controlling.Kata Kunci: Manajemen pendidikan, pembentukan karakter